Digital Transformation and Gen Z Employee Performance: Digital Literacy As Mediator - Nurhatisyah, Nurhatisyah; Wahyuni, Etty Sri; Dewi, Nolla Puspita (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Generation Z, as digital natives comprising approximately 27.94% of Indonesia's population, is rapidly entering the workforce and becoming a significant force in the manufacturing sector. This study investigates the effect of digital transformation on Generation Z employee performance with digital literacy as a mediating variable in manufacturing industries within the Batam Special Economic Zone (SEZ). Batam, strategically positioned near Singapore, is undergoing rapid digital transformation with the development of 10 data centers in Nongsa Digital Park and the adoption of AI-based smart factories. Using a quantitative approach with a survey method, this study collected data from 312 Generation Z employees (born 1997-2012) working in manufacturing companies across Batam's industrial estates. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with Smart PLS 4.0. The findings reveal that: (1) digital transformation has a positive and significant effect on employee performance (β = 0.356, p < 0.001); (2) digital transformation has a positive and significant effect on digital literacy (β = 0.674, p < 0.001); (3) digital literacy has a positive and significant effect on employee performance (β = 0.445, p < 0.001); and (4) digital literacy partially mediates the relationship between digital transformation and employee performance (β = 0.300, p < 0.001). The total effect of digital transformation on employee performance is 0.656, with 45.7% transmitted through digital literacy. These findings provide theoretical contributions to understanding the digital transformation-performance nexus among Generation Z employees and offer practical implications for human resource management strategies in optimizing digital initiatives in manufacturing contexts.